Resistance Rates of Plasmodium Falciparum in Querecotillo, Sullana. January - July 1998 - Bellina, Cecilia (1999)
BACKGROUND: Resistance rates of Plasmodium falciparum in Querecotillo, Sullana, reported by the cohort study for the first semester of 1998, were greater than 50%. OBJECTIVES: To determine the types of Plasmodium falciparum antimicrobial resistance in this district. METHODS: A descriptive, retrospective study in which all malaria cases attended since January 01 to June 30, 1998, was evaluated. RESULTS: Male was the most affected gender (57,4%), and 66,5% of patients were between 15 to 44 years-old. 24,5% of cases was chloroquine-sensible, whereas 75,4% was resistant. Type specific resistance rates found were R1: 29,9%; R2: 13,2% and R3: 32%. CONCLUSION: Resistance rate of Plasmodium falciparum to chloroquine in Querecotillo, was as high as 75%.